2019
DOI: 10.2174/1871520618666180604085612
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Natural Plant Products in the Treatment of Hepatocellular Carcinoma

Abstract: Liver cancer is the fifth most commonly diagnosed cancer and the second leading cause of cancer related deaths worldwide. Among the liver cancers, hepatocellular carcinoma has been reported to be responsible for 85-90% of primary liver cancer and it is the second most common cause of cancer mortality with 700,000 deaths documented annually. The major risk factors of HCC include chronic infections with the hepatitis B (HBV) or hepatitis C (HCV) virus, chronic liver diseases, alcoholism as well as dietary carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 233 publications
0
40
0
1
Order By: Relevance
“…Regardless of its effectiveness, liver cancer cells are able to develop sorafenib resistance after sustained administration [17], where several TKIs (regorafenib and cabozantinib) and monoclonal antibodies (nivolumab, pembrolizumab and ramucirumab) have been recently approved [16]. Considering toxicity and adverse reactions caused by these chemotherapeutic agents, some investigations have focused on the study of antitumor effects of natural compounds against HCC, such as resveratrol, curcumin and melatonin [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of its effectiveness, liver cancer cells are able to develop sorafenib resistance after sustained administration [17], where several TKIs (regorafenib and cabozantinib) and monoclonal antibodies (nivolumab, pembrolizumab and ramucirumab) have been recently approved [16]. Considering toxicity and adverse reactions caused by these chemotherapeutic agents, some investigations have focused on the study of antitumor effects of natural compounds against HCC, such as resveratrol, curcumin and melatonin [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, natural products have served significant roles in the development of anticancer agents (5,6). Resveratrol (trans-3,4',5-trihydroxystilbene) was originally isolated from the roots of white hellebore at 1940 (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several anticancer drugs, such as vinblastine, teniposide, camptothecin, docetaxel, etoposide, and paclitaxel, have been either identified in natural sources or synthesized by modification of molecules having natural origins [6,7]. Numerous natural products, including phytochemicals of dietary and non-dietary origin, have been shown to modulate various signaling pathways linked to hepatocarcinogenesis in vitro and in vivo, which could be valuable for the prevention and treatment of HCC [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the available literature presented here, polyphenols could be considered as potent autophagy modulators for HCC therapy. Although numerous in vitro and in vivo studies have reported the beneficial roles of polyphenols in treating HCC [8][9][10][11][12][13][14][15][16], there are hardly any clinical trials to realize the full potential of preclinical studies. For this purpose, it is worthwhile to explore polyphenols alone or in combination with approved drugs for the treatment of human HCC.…”
Section: Introductionmentioning
confidence: 99%